Just Another Ole Integral

Calculus Level 3

1 ( x 2 + 1 ) 4 d x \large \int_{-\infty}^{\infty}\frac{1}{(x^2+1)^4}\,dx

The integral above can be expressed as 5 a π b 2 c \displaystyle\frac{5^a \pi^b}{2^c} , where a a , b b and c c are integers. What is a + b + c a+b+c ?


The answer is 6.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

Chew-Seong Cheong
Aug 21, 2018

Relevant wiki: Beta Function

I = 1 ( x 2 + 1 ) 4 d x Since the integrand is even = 2 0 1 ( x 2 + 1 ) 4 d x Let u = x 2 d u = 2 x d x = 0 u 1 2 ( 1 + u ) 4 d u Beta function B ( m , n ) = 0 u m 1 ( 1 + u ) m + n d u = B ( 1 2 , 7 2 ) and B ( m , n ) = Γ ( m ) Γ ( n ) Γ ( m + n ) , = Γ ( 1 2 ) Γ ( 7 2 ) Γ ( 4 ) where Γ ( ) is gamma function. = π ( 5 2 × 3 2 × 1 2 π ) 3 ! = 5 π 16 \begin{aligned} I & = \int_{-\infty}^\infty \frac 1{(x^2+1)^4} dx & \small \color{#3D99F6} \text{Since the integrand is even} \\ & = 2 \int_0^\infty \frac 1{(x^2+1)^4} dx & \small \color{#3D99F6} \text{Let }u = x^2 \implies du = 2x\ dx \\ & = \int_0^\infty \frac {u^{-\frac 12}}{(1+u)^4} du & \small \color{#3D99F6} \text{Beta function }B(m,n) = \int_0^\infty \frac {u^{m-1}}{(1+u)^{m+n}} du \\ & = B \left(\frac 12, \frac 72\right) & \small \color{#3D99F6} \text{and }B(m,n) = \frac {\Gamma (m)\Gamma (n)}{\Gamma(m+n)}, \\ & = \frac {\Gamma\left(\frac 12\right)\Gamma\left(\frac 72\right)}{\Gamma(4)} & \small \color{#3D99F6} \text{where }\Gamma (\cdot) \text{ is gamma function.} \\ & = \frac {\sqrt \pi \left(\frac 52 \times \frac 32 \times \frac 12 \sqrt \pi \right)}{3!} \\ & = \frac {5\pi}{16} \end{aligned}

Therefore, a + b + c = 1 + 1 + 4 = 6 a+b+c = 1+1+4 = \boxed 6 .

@Chew-Seong Cheong This is Just the method which I had told Vincent Moroney in his solution about......!!

Aaghaz Mahajan - 2 years, 9 months ago
Naren Bhandari
Aug 21, 2018

Before to evaluate let's reduce the integral in the form of I n 1 ( a 2 + x 2 ) n + 1 d x n N 0 . I_n \int \dfrac{1}{\,(a^2+x^2)^{n+1}}\,dx\qquad \forall n \in\mathbb N \geq 0 \,. Here we will integrate it by parts so let us make u u substitution as u = 1 ( a 2 + x 2 ) n u = \dfrac{1}{\,(a^2+x^2)^n} and d v = d u \,dv =\,du which follows as d u = 2 n x d x ( a 2 + x 2 ) n + 1 \,du = -\dfrac{2n x\,dx}{\,(a^2+x^2)^{n+1}} and v = x v=x . Hence, I n = x ( a 2 + x 2 ) n + 2 n x 2 ( a 2 + x 2 ) n + 1 d x = x ( a 2 + x 2 ) + 2 n a 2 + x 2 a 2 ( a 2 + x 2 ) n + 1 = x ( a 2 + x 2 ) + 2 n I n 2 n a 2 I n + 1 I n + 1 = 1 2 n a 2 x ( a 2 + x 2 ) n + 2 n 1 2 n a 2 I n \begin{aligned} I_n & = \dfrac{x}{\,(a^2+x^2)^n } +2n \int\dfrac{x^2}{\,(a^2+x^2)^{n+1}}\,dx \\& = \dfrac{x}{\,(a^2+x^2)}+ 2n\int \dfrac{\,a^2+x^2-a^2}{\,(a^2+x^2)^{n+1} } \\& = \dfrac{x}{\,(a^2+x^2)}+2nI_n -2na^2I_{n+1} \\ \therefore I_{n+1}& =\dfrac{1}{2na^2} \cdot \dfrac{x}{\,(a^2+x^2)^n}+\dfrac{2n-1}{2na^2} \cdot I_n\end{aligned} Set n = 3 n=3 and a = 1 a=1 we obtain I 4 = 1 6 x ( 1 + x 2 ) 4 + 5 6 I 3 I_4 = \dfrac{1}{6} \cdot \dfrac{x}{\,(1+x^2)^4}+\dfrac{5}{6} \cdot I_3 It is known that 1 a 2 + x 2 = 1 a tan 1 x a + C 1 1 + x 2 = tan 1 x + C I 2 = I 1 + 1 = x 2 ( 1 + x 2 ) + 1 2 tan 1 x + C \begin{aligned}\int\dfrac{1}{a^2+x^2} & = \dfrac{1}{a} \tan ^{-1} \dfrac{x}{a} +C\Rightarrow\int\dfrac{1}{1+x^2} = \tan ^{-1} x +C\\ I_2 =I_{1+1} & =\dfrac{x}{2\,(1+x^2)} +\dfrac{1}{2}\tan^{-1} x +C \end{aligned} Therefore, I 4 = 1 6 x ( 1 + x 2 ) 4 + 5 6 ( 1 4 x ( 1 + x 2 ) 2 + 3 x 8 ( 1 + x 2 ) + 3 8 tan 1 x + C ) I_4 = \dfrac{1}{6} \cdot \dfrac{x}{\,(1+x^2)^4}+\dfrac{5}{6} \cdot \left(\dfrac{1}{4x\,(1+x^2)^2}+\dfrac{3x}{8\,(1+x^2)}+\dfrac{3}{8}\tan ^{-1} x+ C \right) Set the upper and lower limit we obtain I 4 = 1 ( 1 + x 2 ) 4 d x = 5 6 3 8 2 π 2 = 5 1 π 1 2 4 I_4 =\int_{-\infty}^{\infty} \dfrac{1}{\,(1+x^2)^4}\,dx =\dfrac{5}{6}\cdot \dfrac{3}{8} \cdot \dfrac{2\pi}{2} =\dfrac{5^1\cdot \pi^1 }{2^4} Finally, a + b + c = 6 a+b+c = \boxed{6} .

Joseph Newton
Aug 20, 2018

I = 2 0 1 ( x 2 + 1 ) 4 d x = 2 0 1 ( 1 u 2 + 1 ) 4 d u u 2 letting x = 1 u = 2 0 1 u 2 ( 1 + u 2 ) 4 u 8 d u = 2 0 u 6 ( u 2 + 1 ) 4 d u I = 2 0 x 6 ( x 2 + 1 ) 4 d x 2 I = 2 0 x 6 + 1 ( x 2 + 1 ) 4 d x by adding I = 2 0 1 ( x 2 + 1 ) 4 d x I = 0 ( x 2 + 1 ) ( x 4 x 2 + 1 ) ( x 2 + 1 ) 4 d x = 0 ( x 2 + 1 ) 2 3 x 2 ( x 2 + 1 ) 3 d x = 0 1 x 2 + 1 3 x 2 ( x 2 + 1 ) 3 d x = 0 π 2 ( 1 tan 2 θ + 1 3 tan 2 θ ( tan 2 θ + 1 ) 3 ) sec 2 θ d θ letting x = tan θ = 0 π 2 ( 1 sec 2 θ 3 tan 2 θ ( sec 2 θ ) 3 ) sec 2 θ d θ = 0 π 2 1 3 sin 2 θ cos 2 θ d θ = 0 π 2 1 3 4 ( 2 sin θ cos θ ) 2 d θ = 0 π 2 1 3 4 sin 2 2 θ d θ using sin 2 θ = 2 sin θ cos θ = 0 π 2 1 3 8 ( 1 cos 2 θ ) d θ using sin 2 θ = 1 2 ( 1 cos 2 θ ) = 0 π 2 5 8 + 3 8 cos 2 θ d θ = [ 5 8 + 3 16 sin 2 θ ] 0 π 2 = 5 π 16 \begin{aligned}I&=2\int_0^\infty\frac1{(x^2+1)^4}dx\\ &=2\int_\infty^0\frac1{(\frac1{u^2}+1)^4}\frac{-du}{u^2}&&\text{letting }x=\frac1u\\ &=2\int_0^\infty\frac1{u^2\frac{(1+u^2)^4}{u^8}}du\\ &=2\int_0^\infty\frac{u^6}{(u^2+1)^4}du\\ I&=2\int_0^\infty\frac{x^6}{(x^2+1)^4}dx\\ \therefore 2I&=2\int_0^\infty\frac{x^6+1}{(x^2+1)^4}dx&&\text{by adding }I=2\int_0^\infty\frac1{(x^2+1)^4}dx\\ I&=\int_0^\infty\frac{(x^2+1)(x^4-x^2+1)}{(x^2+1)^4}dx\\ &=\int_0^\infty\frac{(x^2+1)^2-3x^2}{(x^2+1)^3}dx\\ &=\int_0^\infty\frac{1}{x^2+1}-\frac{3x^2}{(x^2+1)^3}dx\\ &=\int_0^{\frac\pi2}\left(\frac{1}{\tan^2\theta+1}-\frac{3\tan^2\theta}{(\tan^2\theta+1)^3}\right)\sec^2\theta d\theta&&\text{letting }x=\tan\theta\\ &=\int_0^{\frac\pi2}\left(\frac{1}{\sec^2\theta}-\frac{3\tan^2\theta}{(\sec^2\theta)^3}\right)\sec^2\theta d\theta\\ &=\int_0^{\frac\pi2}1-3\sin^2\theta\cos^2\theta d\theta\\ &=\int_0^{\frac\pi2}1-\frac34(2\sin\theta\cos\theta)^2d\theta\\ &=\int_0^{\frac\pi2}1-\frac34\sin^22\theta d\theta&&\text{using }\sin2\theta=2\sin\theta\cos\theta\\ &=\int_0^{\frac\pi2}1-\frac38(1-\cos2\theta)d\theta&&\text{using }\sin^2\theta=\frac12(1-\cos2\theta)\\ &=\int_0^{\frac\pi2}\frac58+\frac38\cos2\theta d\theta\\ &=\left[\frac58+\frac3{16}\sin2\theta\right]_0^{\frac\pi2}\\ &=\frac{5\pi}{16}\end{aligned}

Vincent Moroney
Aug 20, 2018

Let's consider the complex valued function 1 ( z 2 + 1 ) 4 \frac{1}{(z^2+1)^4} . This has poles at z = ± i z=\pm i . Let Γ \Gamma be the contour containing z = i z=i and the entire real axis. Therefore we have Γ 1 ( z 2 + 1 ) 4 d z = Γ 1 ( z + i ) 4 ( z i ) 4 d z . \oint_{\Gamma} \frac{1}{(z^2+1)^4} \,dz =\oint_{\Gamma} \frac{\frac{1}{(z+i)^4}}{(z-i)^4}\,dz. The Cauchy integral formula for derivatives states f ( λ ) ( z ) = λ ! 2 π i Γ f ( t ) ( t z ) λ + 1 d t f^{(\lambda)}(z) = \frac{\lambda !}{2\pi i} \oint_{\Gamma} \frac{f(t)}{(t-z)^{\lambda +1}} \,dt Some simple rearranging gives 2 π i f λ ( z ) λ ! = Γ f ( t ) ( t z ) λ + 1 d t . \frac{2\pi i f^{\lambda}(z)}{\lambda !} = \oint_{\Gamma} \frac{f(t)}{(t-z)^{\lambda +1}} \,dt. Note that in our case, z = i z=i , λ = 3 \lambda = 3 and f ( 3 ) ( i ) = 120 2 7 i 7 = 15 16 i f^{(3)}(i) = \frac{-120}{2^7i^7} = \frac{15}{16i} . Therefore 1 ( x 2 + 1 ) 4 d x = Γ 1 ( z + i ) 4 ( z i ) 4 d z = 2 π i f λ ( z ) λ ! = 5 π 16 . \int_{-\infty}^{\infty}\frac{1}{(x^2+1)^4}\,dx = \oint_{\Gamma} \frac{\frac{1}{(z+i)^4}}{(z-i)^4}\,dz = \frac{2\pi i f^{\lambda}(z)}{\lambda !} = \frac{5\pi}{16}. Therefore a + b + c = 6 a+b+c = \boxed{6} .

@Vincent Moroney OR, we can substitute x as tan(theta) and then use Beta Function........!!!!

Aaghaz Mahajan - 2 years, 9 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...